Multi-element eutectic phase-change material, phase-change slow-release salt-storage filler and preparation method of multi-element eutectic phase-change material
By covering the surface of the salt storage filler, the temperature regulation of the salt release rate is achieved, and the potential harm of concentrated salt release to the environment in the prior art is solved, which improves environmental friendliness and extends service life.
Patent Information
- Application Number
- CN202411728262.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art still has great room for improvement in the regulation of the release of sustained-release salts and environmental friendliness, especially in high temperature and rainfall conditions, salt may be released in a concentrated manner, resulting in environmental pollution.
The polyeutectic phase change material is used to synthesize a certain proportion of polyeutectic phase change material composed of fatty acids and fatty acid methyl esters, and integrate it on the surface of the salt storage filler to automatically adjust the salt release rate according to the ambient temperature changes.
Effectively control the release rate of salt, reduce the concentrated release of salt during high temperatures and rainfall, reduce environmental pollution, and extend the service life of salt storage fillers.
Smart Images

Figure CN119505809A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of asphalt, and in particular to a multi-element eutectic phase change material, a phase change slow-release salt storage filler and a preparation method thereof. Background Art
[0002] Winter road icing is a major hidden danger to traffic safety and poses a serious threat to drivers. In winter road deicing operations, the use of slow-release salt-based materials is an effective solution. Compared with traditional mineral powder fillers, this material uses porous carriers to store salt and achieves slow release through its unique structural design. In rainy and snowy weather, when precipitation penetrates into the road surface, it causes the salt in the porous filler to ionize at the water-ice interface, thereby lowering the freezing point of the aqueous solution. This process enables the melted salt solution to further penetrate into the tiny cracks in the road surface, helping to improve the deicing effect. At the same time, the slow-release salt-based material gradually releases salt along the salt precipitation channel by combining the dual effects of chemical dissolution and mechanical abrasion, continuously melting ice and snow and effectively inhibiting road icing.
[0003] In existing research, some scholars are committed to improving the storage and release technology of slow-release salt. For example, some studies have used resin materials (such as epoxy resin) to wrap sodium chloride particles and control the release rate of salt by adjusting the thickness of the resin, but found that its release effect is greatly affected by temperature and mechanical action. High temperature and frequent vehicle rolling may accelerate the aging and damage of the resin, resulting in rapid release of salt. Other studies have tried to use silane compounds or oily substances to wrap salt to enhance the hydrophobicity of the material and slow down the infiltration of water into salt particles. However, this type of technology has shown great shortcomings in areas with high rainfall, especially long-term rainfall may lead to the loss of the surface oil layer, causing the salt to be released in a concentrated manner in a short period of time.
[0004] In addition, some studies have developed polymer coatings with temperature-sensitive properties to adjust the release rate of salt through the thermal expansion of the material, but experiments have shown that the reliability of such materials is limited. Under low temperature conditions, the hardening effect of the polymer may hinder the release of salt, while under high temperature conditions, the release rate will be significantly accelerated, resulting in uneven release.
[0005] The common shortcoming of the existing technologies is that they fail to effectively solve the potential harm to the environment caused by concentrated release of salt. In hot and rainy weather, due to the scouring effect caused by vehicle driving, a large amount of salt deposition may be concentrated on the road surface and lost to the surrounding environment with rainwater. This salt seeps into the road slopes and nearby soil, not only destroying vegetation, but also polluting groundwater, posing a potential threat to the ecosystem. These problems show that the current technology still has a lot of room for improvement in the release regulation and environmental friendliness of slow-release salts. Therefore, the development of a slow-release salt-based material that can automatically adjust the salt release rate according to changes in ambient temperature and reduce environmental pollution has become a hot spot and key direction of current research. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides a multi-element eutectic phase change material, a phase change slow-release salt storage filler and a preparation method, by synthesizing the multi-element eutectic phase change material and integrating it on the surface of the salt storage filler to achieve the control of the release rate of salt. The multi-element eutectic phase change material itself has a hydrophobic property. When the ambient temperature is lower than the phase change temperature, the multi-element eutectic phase change material covering the surface of the salt storage filler solidifies from liquid to solid, and the microcracks on the solid surface become microchannels that promote the release of salt; when the temperature is higher than the phase change temperature, the solid phase changes to liquid, the microchannels are closed, and the release of salt is hindered.
[0007] The present invention is achieved through the following technical solutions: A multi-element eutectic phase change material comprises, by weight, 30-70 parts of fatty acid phase change material and 30-70 parts of fatty acid methyl ester phase change material.
[0008] Preferably, the fatty acid phase change material is one of decanoic acid, undecanoic acid, dodecanoic acid and tridecanoic acid.
[0009] Preferably, the fatty acid methyl ester phase change material is one of methyl pentadecanoate, methyl hexadecanoate, methyl heptadecanoate and methyl octadecanoate.
[0010] A method for preparing a multi-element eutectic phase change material comprises the following steps: Step 1, by weight, 30-70 parts of fatty acid phase change material and 30-70 parts of fatty acid methyl ester phase change material are mixed uniformly to obtain a mixture; Step 2: Heat and melt the mixture, and react at a constant temperature of 50-60° C. for 2-3 hours to obtain a multi-element eutectic phase change material.
[0011] A phase-change slow-release salt storage filler, comprising a salt storage filler core, on which a multi-element eutectic phase-change material and polystyrene are sequentially coated; Calculated by weight, it includes 20-30 parts of porous minerals, 30-60 parts of salt, 0.5-1 parts of anti-corrosion agent, 1-2 parts of silane oil, 2-5 parts of polystyrene, and 1-2 parts of multi-element eutectic phase change material.
[0012] Preferably, the anti-corrosion agent is triethanolamine hydrochloride and 1'3-bis(hydroxymethyl)urea.
[0013] Preferably, the silane oil is methyl silane oil.
[0014] A method for preparing a temperature-controlled slow-release salt storage filler comprises the following steps: Step 1: Mix 20-30 parts of porous mineral, 30-60 parts of salt and 0.5-1 part of corrosion inhibitor by weight, so that the salt particles fill the pores of the porous mineral to obtain a salt storage filler; Step 2: Put the salt storage filler obtained in step 1 and 1-2 parts of multi-element eutectic phase change material into anhydrous ethanol for mixing, so that the multi-element eutectic phase change material covers the surface of the salt storage filler to obtain a phase change salt storage filler; Step 3, adding the phase-change salt storage filler obtained in step 2 and 2 to 5 parts of polystyrene into cyclohexane for mixing, so that the polystyrene covers the surface of the phase-change salt storage filler to obtain a resin salt storage filler; Step 4: air-dry and clean the resin salt storage filler to obtain a phase-change slow-release salt storage filler.
[0015] Preferably, the air-drying and cleaning method of the resin salt storage filler in step 4 is as follows: The product is air-dried at a temperature above 40°C, and the air-dried product is then put into silane oil and washed with petroleum ether to obtain a phase-change slow-release salt storage filler.
[0016] An asphalt comprises the phase-changing slow-release salt storage filler.
[0017] Compared with the prior art, the present invention has the following beneficial technical effects: The present application provides a multi-element eutectic phase change material, which is composed of a certain proportion of fatty acids and fatty acid methyl esters. When the temperature is lower than the lower phase transition temperature, the multi-element eutectic phase change material changes from a liquid to a solid, causing the polymer to expand and crack, and the microcracks on the solid surface become microchannels that promote the release of salt. On the contrary, when the temperature exceeds the phase transition temperature, the multi-element eutectic phase change material changes from a solid to a liquid, causing the hydrophobic multi-element eutectic phase change material liquid to cover the entire salt storage filler, thereby reducing the release of salt during the rainy period in summer.
[0018] The present invention provides a phase-change slow-release salt storage filler, which includes porous minerals, salt, corrosion inhibitors, silane oil, polystyrene and multi-element eutectic phase change materials; the multi-element eutectic phase change material itself has hydrophobic properties. When the ambient temperature is lower than the phase change temperature, the multi-element eutectic phase change material covering the surface of the salt storage filler solidifies from liquid to solid, and the microcracks on the solid surface become microchannels that promote the release of salt; when the temperature is higher than the phase change temperature, the solid phase changes to liquid, the microchannels are closed, and the release of salt is hindered. A small amount of corrosion inhibitor and silane oil are added to avoid the precipitated salt from causing damage to road facilities while improving the hydrophobic effect of the salt storage filler. The phase-change slow-release salt storage filler can reduce the accumulation of a large amount of salt precipitation on the surface of the slow-release deicing road due to water washing caused by vehicles during high temperatures and rainfall, and at the same time extend the service life of the salt storage filler.
[0019] The preparation method of the phase-change slow-release salt storage filler provided by the present invention can use solid waste, silane oil, polystyrene and other low-priced materials as porous minerals, so that the salt storage filler has good economic value, and the preparation process of the temperature-controlled slow-release salt storage filler is simple and the production cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 This is a test diagram of the electrical conductivity of the phase-change slow-release salt storage filler of the present invention. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.
[0023] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0024] A multi-element eutectic phase change material comprises, by weight, 30-70 parts of fatty acid phase change material and 30-70 parts of fatty acid methyl ester phase change material.
[0025] The fatty acid phase change material is one of decanoic acid, undecanoic acid, dodecanoic acid and tridecanoic acid.
[0026] The fatty acid methyl ester phase change material is one of methyl pentadecanoate, methyl hexadecanoate, methyl heptadecanoate and methyl octadecanoate.
[0027] If the ratio of fatty acid phase change material to fatty acid methyl ester phase change material is too high, the synthesized multi-element eutectic phase change material will be unsuitable for the asphalt pavement environment. If the ratio is too low, the multi-element eutectic phase change material will be not resistant to high temperatures and cannot be used for asphalt pavement.
[0028] Correspondingly, the present application also provides a method for preparing a multi-element eutectic phase change material, comprising the following steps: Step 1, by weight, comprising 30-70 parts of fatty acid phase change material and 30-70 parts of fatty acid methyl ester phase change material and mixing them; Step 2: Heat and melt the mixture obtained in step 1, and react at a constant temperature of 50-60° C. for 2-3 hours to evenly mix the fatty acid phase change material and the fatty acid methyl ester phase change material to obtain a multi-element eutectic phase change material.
[0029] A phase-change slow-release salt storage filler, comprising a salt storage filler core, on which a multi-element eutectic phase-change material and polystyrene are sequentially coated; Calculated by weight, it includes 20 to 30 parts of porous minerals, 30 to 60 parts of salt, 0.5 to 1 part of anti-corrosion agent, 1 to 2 parts of silane oil, 1 to 2 parts of multi-element eutectic phase change material, and 2 to 5 parts of polystyrene.
[0030] The particle size of porous minerals should be less than 0.15 mm and the porosity should be greater than 20% to allow sufficient space to store salt.
[0031] The salt content should mainly be chloride.
[0032] The corrosion inhibitor should mainly reduce chlorine corrosion, and triethanolamine hydrochloride and 1'3-bis(hydroxymethyl)urea are preferred.
[0033] Silane oil is mainly methyl silane oil.
[0034] The phase-change slow-release salt storage filler is prepared by synthesizing a multi-eutectic phase change material, which is composed of a certain proportion of fatty acids and fatty acid methyl esters. When the temperature is lower than the lower phase change temperature, the multi-eutectic phase change material changes from liquid to solid, causing the polymer to expand and crack, and the microcracks on the solid surface become microchannels that promote the release of salt. On the contrary, when the temperature exceeds the phase change temperature, the multi-eutectic phase change material changes from solid to liquid, causing the hydrophobic multi-eutectic phase change material liquid to cover the entire salt storage filler, thereby reducing the release of salt during rainy periods in summer. The problem that a large amount of salt precipitation will accumulate on the surface of the slow-release deicing road due to water washing caused by vehicles during high temperatures and rainfall is solved, while extending the service life of the salt storage filler.
[0035] Based on the above phase-change slow-release salt storage filler, the present application also provides a method for preparing a phase-change slow-release salt storage filler, comprising the following steps: Step 1: Mix 20-30 parts of porous mineral, 30-60 parts of salt and 0.5-1 part of corrosion inhibitor by weight, so that the salt particles fill the pores of the porous mineral to obtain a salt storage filler; Step 2: Mix 30-50 parts of fatty acid phase change material and 50-70 parts of fatty acid methyl ester phase change material, and stir at 60° C. for 2 hours to obtain a multi-element eutectic phase change material.
[0036] Step 3, the salt storage filler obtained in step 1 and 1-2 parts of the multi-element eutectic phase change material obtained in step 2 are put into anhydrous ethanol for mixing, so that the multi-element eutectic phase change material covers the surface of the salt storage filler, thereby obtaining a phase change salt storage filler; Step 4, adding the phase-change salt storage filler obtained in step 3 and 2 to 5 parts of polystyrene into cyclohexane for mixing, so that the polystyrene covers the surface of the phase-change salt storage filler to obtain a resin salt storage filler; Step 5: air-dry and clean the resin salt storage filler to obtain a phase-change slow-release salt storage filler.
[0037] Example 1 A method for preparing a phase-change slow-release salt storage filler comprises the following steps: Step 1: Mix 20 parts of porous mineral, 30 parts of salt and 0.5 parts of corrosion inhibitor by weight, so that the salt particles fill the pores of the porous mineral to obtain a salt storage filler; Step 2: Mix 30 parts of fatty acid phase change material and 70 parts of fatty acid methyl ester phase change material, and stir at 60° C. for 2 hours to obtain a multi-element eutectic phase change material.
[0038] Step 3, the salt storage filler obtained in step 1 and one portion of the multi-element eutectic phase change material obtained in step 2 are put into anhydrous ethanol for mixing, so that the multi-element eutectic phase change material covers the surface of the salt storage filler, thereby obtaining a phase change salt storage filler; Step 4, adding the phase-change salt storage filler obtained in step 3 and 2 parts of polystyrene into cyclohexane and mixing them, so that the polystyrene covers the surface of the phase-change salt storage filler; Step 5: Place the solution and the pre-product in step 4 into an asphalt rotary film aging box, heat and air-dry, and then put the obtained product into silane oil, wash it with petroleum ether, and then filter it to obtain a phase-change slow-release salt storage filler.
[0039] Example 2 A method for preparing a phase-change slow-release salt storage filler comprises the following steps: Step 1: Mix 25 parts of porous mineral, 40 parts of salt and 0.7 parts of corrosion inhibitor by weight, so that the salt particles fill the pores of the porous mineral to obtain a salt storage filler; Step 2: Mix 40 parts of fatty acid phase change material and 60 parts of fatty acid methyl ester phase change material, and stir at 60° C. for 2 hours to obtain a multi-element eutectic phase change material.
[0040] Step 3, the salt storage filler obtained in step 1 and 1.5 parts of the multi-element eutectic phase change material obtained in step 2 are added into anhydrous ethanol and mixed, so that the multi-element eutectic phase change material covers the surface of the salt storage filler, thereby obtaining a phase change salt storage filler; Step 4, adding the phase-change salt storage filler obtained in step 3 and 3 parts of polystyrene into cyclohexane and mixing them, so that the polystyrene covers the surface of the phase-change salt storage filler; Step 5: Place the solution and the pre-product in step 4 into an asphalt rotary film aging box, heat and air-dry, and then put the obtained product into silane oil, wash it with petroleum ether, and then filter it to obtain a phase-change slow-release salt storage filler.
[0041] Example 3 A method for preparing a phase-change slow-release salt storage filler comprises the following steps: Step 1: Mix 30 parts of porous mineral, 60 parts of salt and 1 part of corrosion inhibitor by weight, so that the salt particles fill the pores of the porous mineral to obtain a salt storage filler; Step 2: Mix 50 parts of fatty acid phase change material and 50 parts of fatty acid methyl ester phase change material, and stir at 60° C. for 2 hours to obtain a multi-element eutectic phase change material.
[0042] Step 3, the salt storage filler obtained in step 1 and two parts of multi-element eutectic phase change material obtained in step 2 are put into anhydrous ethanol and mixed, so that the multi-element eutectic phase change material covers the surface of the salt storage filler, thereby obtaining a phase change salt storage filler; Step 4, adding the phase-change salt storage filler obtained in step 3 and 5 parts of polystyrene into cyclohexane and mixing them, so that the polystyrene covers the surface of the phase-change salt storage filler; Step 5: Place the solution and the pre-product in step 4 into an asphalt rotary film aging box, heat and air-dry, and then put the obtained product into silane oil, wash it with petroleum ether, and then filter it to obtain a phase-change slow-release salt storage filler.
[0043] Example 4 A method for preparing a phase-change slow-release salt storage filler comprises the following steps: Step 1: Mix 20 parts of porous mineral, 30 parts of salt and 0.8 parts of corrosion inhibitor by weight, so that the salt particles fill the pores of the porous mineral to obtain a salt storage filler; Step 2: Mix 60 parts of fatty acid phase change material and 40 parts of fatty acid methyl ester phase change material, and stir at 60° C. for 2 hours to obtain a multi-element eutectic phase change material.
[0044] Step 3, the salt storage filler obtained in step 1 and 0.9 parts of the multi-element eutectic phase change material obtained in step 2 are added into anhydrous ethanol for mixing, so that the multi-element eutectic phase change material covers the surface of the salt storage filler, thereby obtaining a phase change salt storage filler; Step 4, adding the phase-change salt storage filler obtained in step 3 and 2.5 parts of polystyrene into cyclohexane and mixing them, so that the polystyrene covers the surface of the phase-change salt storage filler; Step 5: Place the solution and the pre-product in step 4 into an asphalt rotary film aging box, heat and air-dry, and then put the obtained product into silane oil, wash it with petroleum ether, and then filter it to obtain a phase-change slow-release salt storage filler.
[0045] Correspondingly, the present application also provides an asphalt comprising the above-mentioned temperature-controlled slow-release salt storage filler.
[0046] Test on salt release rate of phase-changing slow-release salt storage filler. The salt release rate control performance of commercially available Ma Feilong and the phase-change slow-release salt storage filler prepared in Examples 1 to 4 was tested. The salt release rate of the temperature-controlled slow-release salt storage filler prepared in Examples 1 to 4 was quantitatively analyzed. It was measured by filling a beaker with 250 ml of pure water and placing it in a water bath at an appropriate temperature. At the beginning of the test, 2.5 g of Ma Feilong and the temperature-controlled slow-release salt storage filler were evenly sprinkled on the water surface of the beaker, and the conductivity of the solution was measured at the corresponding time. The performance test results are shown in Figure 1 .
[0047] The greater the conductivity, the faster the salt release rate. Figure 1It can be seen from the test results that Ma Feilong does not have a temperature regulation function, so its conductivity changes linearly with the increase in temperature. The phase-change slow-release salt storage filler of the present invention has a higher conductivity than Ma Feilong when the temperature is below a specific temperature; however, when the temperature is above a specific temperature, the conductivity is lower than that of Ma Feilong. This proves that the phase-change slow-release salt storage filler of the present invention has the function of regulating the salt release rate at temperature. The specific temperature of the temperature-controlled slow-release salt storage filler is related to the ratio of fatty acids and fatty acid methyl esters.
[0048] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A multi-element eutectic phase change material, characterized in that: By mass, 30-70 parts of fatty acid phase change material and 30-70 parts of fatty acid methyl ester phase change material.
2. The multi-element eutectic phase change material according to claim 1, characterized in that: The fatty acid phase change material is one of decanoic acid, undecanoic acid, dodecanoic acid and tridecanoic acid.
3. A multi-element eutectic phase change material according to claim 1 or 2, characterized in that: The fatty acid methyl ester phase change material is one of methyl pentadecanoate, methyl hexadecanoate, methyl heptadecanoate and methyl octadecanoate.
4. A method for preparing the multi-element eutectic phase change material according to any one of claims 1 to 3, characterized in that: The process includes: Step 1, by weight, 30-70 parts of fatty acid phase change material and 30-70 parts of fatty acid methyl ester phase change material are mixed uniformly to obtain a mixture; Step 2: Heat and melt the mixture, and react at a constant temperature of 50-60° C. for 2-3 hours to obtain a multi-element eutectic phase change material.
5. A phase-change slow-release salt storage filler, characterized in that: A salt storage filler inner core is coated with a multi-element eutectic phase change material and polystyrene in sequence; Calculated by weight, it includes 20 to 30 parts of porous minerals, 30 to 60 parts of salt, 0.5 to 1 part of anti-corrosion agent, 1 to 2 parts of silane oil, 2 to 5 parts of polystyrene, and 1 to 2 parts of multi-element eutectic phase change material according to any one of claims 1 to 3.
6. The phase-change slow-release salt storage filler according to claim 5, characterized in that: The anti-corrosion agents are triethanolamine hydrochloride and 1'3-bis(hydroxymethyl)urea.
7. The phase-change slow-release salt storage filler according to claim 5, characterized in that: The silane oil is methyl silane oil.
8. A method for preparing the temperature-controlled slow-release salt storage filler according to any one of claims 5 to 7, characterized in that: The following steps are involved: Step 1: Mix 20-30 parts of porous mineral, 30-60 parts of salt and 0.5-1 part of corrosion inhibitor by weight, so that the salt particles fill the pores of the porous mineral to obtain a salt storage filler; Step 2: Put the salt storage filler obtained in step 1 and 1-2 parts of multi-element eutectic phase change material into anhydrous ethanol for mixing, so that the multi-element eutectic phase change material covers the surface of the salt storage filler to obtain a phase change salt storage filler; Step 3, adding the phase-change salt storage filler obtained in step 2 and 2 to 5 parts of polystyrene into cyclohexane for mixing, so that the polystyrene covers the surface of the phase-change salt storage filler to obtain a resin salt storage filler; Step 4: air-dry and clean the resin salt storage filler to obtain a phase-change slow-release salt storage filler.
9. The method for preparing the temperature-controlled slow-release salt storage filler according to claim 8, characterized in that: The air-drying and cleaning method of the resin salt storage filler in step 4 is as follows: The product is air-dried at a temperature above 40°C, and the air-dried product is then put into silane oil and washed with petroleum ether to obtain a phase-change slow-release salt storage filler.
10. Asphalt, characterized in that: It comprises the phase-changing slow-release salt storage filler as described in any one of claims 5-7.